Cognitive Performance of Patients With Multiple Sclerosis and Optic Neuritis at Presentation - Leshno, Ari; Sagiv, Oded; Aloni, Roy; Skaat, Alon; Achiron, Anat; Huna-Baron, Ruth (Journal of neuro-ophthalmology, 2022)
Cognitive dysfunction is common among patients with multiple sclerosis (MS), but the effect of coexisting optic neuritis (ON) at the first presentation of multiple sclerosis on the course of cognitive decline is unknown. The purpose of this study was to assess whether ON at presentation has any effect on the progression of cognitive decline in MS. Historical cohort study. We retrospectively compared the cognitive performance of patients with relapsing-remitting MS with and without ON at the time of MS diagnosis. Subjects were included if cognitive test results were available both at baseline and after at least 36 months from presentation and grouped based on the presence (MS-ON) or absence (MS-non-ON) of optic neuritis at presentation. One hundred seventy consecutive subjects with MS were found suitable, with a 1:2 male:female ratio and a mean age at diagnosis of 33.0 ± 10.9 years. Forty-six patients (27.1%) presented with ON. No significant differences were found in cognitive performance at onset between the 2 groups. Both groups had a similar follow-up duration. The prevalence of cognitive decline in the general score was significantly higher in the MS-ON group compared with the MS-non-ON group (6.5% vs 0%, respectively; P < 0.001), as well as in the attention (8.7% vs 1.6%; P = 0.046) and the executive function (17.4% vs 2.4%; P = 0.001) domains. Optic neuritis at presentation of MS is associated with a higher prevalence of cognitive decline over time. Potential benefit of early intervention to prevent cognitive decline may be warranted.